Applying hiPSCs and Biomaterials Towards an Understanding and Treatment of Traumatic Brain Injury - Lacalle-Aurioles, María; Cassel de Camps, Camille; Zorca, Cornelia E.; Beitel, Lenore K.; Durcan, Thomas M. (Frontiers in Cellular Neuroscience, 2020)
Traumatic brain injury (TBI) is the leading cause of disability and mortality in children and young adults and has a profound impact on the socio-economic wellbeing of patients and their families. Initially, brain damage is caused by mechanical stress-induced axonal injury and vascular dysfunction, that can include hemorrhage, blood brain barrier disruption and ischemia. Subsequent neuronal degeneration, chronic inflammation, demyelination and the spread of cytotoxicity can further aggravate disease pathology. Thus, TBI treatment requires prompt intervention to protect against neuronal degeneration. Rapid advances in the field of stem cells (SCs) have revolutionized the prospect of repairing brain function following TBI. For instance, endogenous stimulation or exogenous transplant of SCs, intravascular injection of SC-derived exosomes, and transplant of cerebral organoids have proven beneficial in ameliorating the outcomes of TBI in animal models. Yet translation of these approaches into clinical interventions is still in the early stages of development. In this review, we highlight the important role of stem cell research as an avenue into better understanding TBI-related pathology and developing novel therapeutic approaches, building on where we are currently. We summarize some of the most relevant achievements of regenerative therapies and outline key challenges for TBI treatments that remain to be addressed.